A poética do vernáculo: os painéis de Geraldo Queiroz no Triângulo Mineiro - Machado Junior, Juscelino Humberto Cunha (2010)
The objective of this thesis is to research, document and analyse the production of glass mosaic panels by Geraldo Queiroz an artist from Uberlandia. The study aims to contribute towards filling a gap in this academic field, which historically lacks analysis and documentation of artistic production outside major cities and capitals. It also highlights discussion about the synthesis of art and modernist ideals not only nationwide but also internationally in the second post-war period. The study is also noteworthy due to the shortage of literary references about mosaic art in Brazil despite its importance in the Modern movement. Geraldo Queiroz created several panels that complemented the architecture of a modernist character widespread in the Triangulo Mineiro region in the 1950s. His work was influenced mainly by the activity of architect João Jorge Coury, with whom he worked on many projects. Working within a creative framework shaped by tradition, the artist's work is summarised by glass mosaic panels, with densely figurative compositions, much admired for their ornamental character.